Development of Mobile Phone Addict Scale - Yuwanto, Listyo (Faculty of Psychology, Universitas Surabaya, 2012)
The aim of this study was to develop the mobile phone addict scale, which was developed based on Mobile Phone Addict Index (MPAI) according to Leung’s study (2007), such as inability to control craving, anxiety and feeling lost, withdrawal/escape, and productivity loss. The development of the scale adopted items of Leung’s study. Participants were 200 students who were at late stages of adolescence selected through incidental sampling (N=200). Results of validity, reliability, and norm are further discussed. Penelitian ini bertujuan mengembangkan skala mobile phone addict, yang dikembangkan berdasarkan Mobile Phone Addict Index (MPAI) hasil penelitian Leung (2007), antara lain ketakmampuan mengendalikan ketahigan, kecemasan dan perasaan hilang, penarikan diri/pelarian, dan kehilangan produktivitas. Pengembangan skala mengadopsi butir-butir hasil penelitian Leung. Partisipan adalah mahasiswa yang berada pada tahapan perkembangan remaja akhir melalui incidental sampling (N=200). Hasil uji validitas, reliabilitas, dan norma skala didiskusikan lebih lanjut.